2010
DOI: 10.1007/s00425-010-1120-2
|View full text |Cite
|
Sign up to set email alerts
|

Two similar but distinct second intron fragments from tobacco AGAMOUS homologs confer identical floral organ-specific expression sufficient for generating complete sterility in plants

Abstract: The carpel- and stamen-specific AtAGIP promoter derived from the Arabidopsis AGAMOUS (AG) second intron/enhancer is ideal for engineering complete sterility but it is highly host-specific. To ascertain whether a chimeric promoter with similar tissue specificity can be created for species other than Arabidopsis, we isolated two similar but distinct AG second intron/enhancers from tobacco (NtAGI-1 and NtAGI-2) and analyzed their ability to drive floral organ-specific expression in plants through the creation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…As expected, 94% of rNtAGIP1::DT‐A plants produced floral buds devoid of visible petals, stamens and carpels (Figures b and c,k) in comparison with normal vegetative and floral development exhibited in wild‐type ( Wt ) plants (Figure a,g,h), confirming the tissue specificity of this enhancer/promoter (Yang et al ., ). Also as expected, almost all (91%) of the pBASE ACT ‐transformed plants displayed normal vegetative growth but a self‐sterile phenotype (Figures b and b) with ablated stigmas (Figure i) and collapsed pollen (Figure j), consistent with previous findings in Arabidopsis (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…As expected, 94% of rNtAGIP1::DT‐A plants produced floral buds devoid of visible petals, stamens and carpels (Figures b and c,k) in comparison with normal vegetative and floral development exhibited in wild‐type ( Wt ) plants (Figure a,g,h), confirming the tissue specificity of this enhancer/promoter (Yang et al ., ). Also as expected, almost all (91%) of the pBASE ACT ‐transformed plants displayed normal vegetative growth but a self‐sterile phenotype (Figures b and b) with ablated stigmas (Figure i) and collapsed pollen (Figure j), consistent with previous findings in Arabidopsis (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, rNtAGIP1::DT‐A lines had produced sepals and petals but no visible stamens or carpels by stages 6–7 (Figure g). Petals that had emerged at this point had begun to turn brown by stages 8–9 (Figure h) and eventually died by stage 13 (Figure i), which is consistent with previous findings (Yang et al ., ). Those pAGI1F ACT lines with an activated ablation phenotype showed similar floral morphological defects as rNtAGIP1::DT‐A plants, without visible stamen and carpel primordia by stages 6–7 (Figure m,p).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…pekinensis ) was observed to produce 50% aborted pollen and 50% normal pollen as expected (Kim et al ., ). In subsequent studies, the DT‐A gene was used to engineer male sterility for the purpose of transgene bioconfinement (Liu and Liu, ; Liu et al ., ; Skinner et al ., ; Yang et al ., , ). Although each of these studies reported a high degree of reproductive tissue ablation, only one study reported outcrossing results.…”
Section: Discussionmentioning
confidence: 99%